Design of a magnet to study quench propagation in a Cable-In-Conduit-Conductor filled with stagnant superfluid helium. (July 2022) - Durañona, U.; Abdel Maksoud, W.; Baudouy, B.; Berriaud, C.; Calvelli, V.; Dilasser, G.; Lorin, C.; Lottin, J.-P.; Pontarollo, T.; Stacchi, F.
Highlights: Design of a prototype for a CICC magnet quench studies. Cable-In-Conduit with copper profile filled with stagnant superfluid helium. Numerical quench propagation studies in superfluid helium. Phenomenological study of Thermal-Hydraulic-Quench-Back. Impact of the friction forces in the quench propagation behavior. Abstract: In the dark matter Axion research context, the MADMAX project acts as a figurehead in the physics research field. The goal of the project is to discover axion as dark matter. For this, it is necessary to design and manufacture a dipole, composed of 18 coils, that generates a Figure of Merit of 100 T 2 m 2 . The MADMAX coils have several specific features though, as the use of Cable-In-Conduit-Conductor (CICC) with a copper profile that serves as thermal stabilizer and the use of stagnant superfluid helium inside the CICC conduit. With a 28 mm 2 helium cross-section and a conductor of several hundred meters before reaching the helium bath, the quench dynamics appear then as a challenge of the design phase. To experimentally investigate the quench propagation in the MADMAX coils, we designed a MADMAX-like solenoidal prototype based on numerical simulations made with THEA® called MACQU (MAdmax Coil for Quench Understanding). This numerical study allowed analysing the physics behind the quench phenomenon and define the relevant current range for the experimental quench studies. Nevertheless, as THEA® has never been used for a CICC filled with superfluid helium, the results will have to be benchmarked by the quench testing campaign on MACQU. The different calculations made with THEA® show that the quench propagation is divided into two different phases: after the initiation, the propagation is at a constant speed of around 5 m/s, followed by an acceleration phase where the propagation speed reaches 40 m/s, at 17 kA. Among the different possible phenomena, we have found that the friction forces term, as defined in the THEA code, are responsible for this two-phase propagation because they initiate the pre-heating of the magnet before the quench, reducing then the local temperature margin.